Implementasi Nilai Religius, Moral Etika dan Tradisi dalam Manajemen: Sebuah Tinjauan Literatur - Lazuardi, Dedy; Wahyuni, Putri; Gustina, Ihdina; Mujiatun, Siti (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
This research aims to understand how the application of religious, moral/ethical and traditional values affects organizational performance. It also explores the challenges faced by managers in implementing these values in management practices, as well as how these values can shape an organizational culture that supports sustainability and business ethics. This research uses a qualitative approach, with the Grounded Theory method to develop theories based on empirical data collected. Data collection techniques included interviews, observations, and document analysis, focusing on the phenomenon of applying religious, moral/ethical, and traditional values in the organization. The results show that religious, moral/ethical, and traditional values contribute significantly to improving organizational performance. Religious values such as honesty, justice, and responsibility create a harmonious and productive work environment. Morals/ethics support customer and stakeholder trust, while tradition strengthens organizational culture and employee loyalty. The results show that religious values, morals/ethics, and traditions contribute significantly to improving organizational performance. Religious values such as honesty, justice, and responsibility create a harmonious and productive work environment. Morals/ethics support customer and stakeholder trust, while traditions support organizational performance.